The effect of mothers' emotion‐related responses to adolescent disclosures and adolescent perspective taking on the timing of future disclosures. Issue 3 (24th January 2019) - Disla, Janice; Main, Alexandra; Kashi, Smitha; Boyajian, Jonathan
Abstract: Adolescent disclosure to parents is an important feature of high‐quality parent–adolescent relationships and is associated with positive adolescent adjustment. However, no studies have examined parental emotion‐related responses (ERRs) to disclosures and adolescent dispositional characteristics that may facilitate or inhibit adolescent disclosures during real‐time conversations. The present study tested (a) which maternal ERRs to adolescent disclosures predicted quicker subsequent disclosures during mother–adolescent conversations, and (b) whether adolescent perspective taking moderated these associations. Adolescent disclosures and maternal ERRs were coded moment‐to‐moment during a problem‐solving discussion and adolescents reported on their perspective taking. Multilevel Generalized Linear Mixed‐Effects Models revealed that maternal interest and validation predicted the shortest lag times compared with other maternal ERRs, controlling for adolescent age, gender, total durations of maternal ERRs, and total frequency and duration of adolescent disclosures. Adolescent perspective taking moderated associations between maternal ERRs to adolescent disclosures and lag times. Specifically, adolescents high in perspective taking were most likely to make quicker subsequent disclosures when mothers responded to disclosures with interest. This is the first study to examine how contingent parental responses to adolescent disclosures in real time affect the timing of subsequent disclosures during parent–adolescent conversations.